Estudio comparativo del drenaje linfático manual y el de manga de presoterapia aplicado en mujeres mayores de 40 años con linfedema post mastectomía que asisten al área de Fisioterapia del Hospital SOLCA de Guayaquil . - Benítez Ruiz, Richard Bryan (2019)
Postmastectomy lymphedema is a complication that occurs after the removal of the breast and lymph nodes affected by cancer. Depending on the surgical intervention that is done to treat breast cancer, its incidence and severity varies. As a treatment, there is manual lymphatic drainage or lymphatic drainage with the pressotherapy sleeve, which helps to reduce edema, pain and increase the functionality of the affected limb. The objective of this work is to identify which of the two techniques is more effective, by comparing the results obtained before and after applying these techniques. The present research work is of a deductive nature with a quantitative approach and a correlational and explanatory scope of experimental design of the quasi-experimental type. The population that was evaluated corresponds to 30 women with postmastectomy lymphedema. The results obtained show that both lymphatic drainage techniques give positive results as lymphedema treatment, but manual lymphatic drainage is more effective. In conclusion, it is unquestionable that manual lymphatic drainage is more effective than lymphatic drainage with the pressotherapy sleeve, indicating it as the ideal treatment for postmastectomy lymphedema.